KAJIAN PERBANDINGAN PERFORMANSI ROUTING PROTOCOL RIPNG, OSPFV3 DAN EIGRPV6 PADA JARINGAN IPV6 - Redaksi Tim Jurnal (KILAT, 2018)
The main purpose of IP next generation version 6 or called IPv6 is to meet the needs of IP addresses for the long term. With the presence of IPv6 it is also necessary routing protocol that supports IPv6 network. Routing protocols work to connect between networks, and choose paths or routes to reach other networks. There are three types of routing protocols that already support IPv6 services. Among other types of distance vector (RIPng), link-state (OSPFv3) and hybrid (EIGRPv6). This final project is designed to know the performance of the three types of routing protocols on IPv6 network. Testing is done by analyzing routing update process, ICMPv6 packet analysis and testing by sending Real-time Transport Protocol (RTP) packet in the form of audio video stream sent via server and accessed through client. In the simulation and analysis results using GNS3 (Graphic Network Simulator 3) and wireshark found that the OSPFv3 performance testing is better than EIGRPv6 and RIPng when performing routing updates or when link down occurs. Then the data analysis of test results with the delivery of Real-time Transport Protocol package so that it can be concluded that OSPFv3 algorithm better than EIGRPv6 and RIPng in terms of delay, packet loss, throughput and jitter.